The Organoleptic Quality of Triggerfish Nuggets (Canthidermis maculata) With Hi-Protein Wheat Flour and White Bread Filling - Rifqi Akmal; Yuli Heirina Hamid; Dikki Zulfikar (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Triggerfish (Canthidermis maculata) is a type of demersal fish that is abundant but still minimal in processing, even though this fish has good nutritional value and have soft meat textured, white meat, and cheap price, this characteristic makes triggerfish suitable to be used as processed products such as nuggets. The aim of this study was to identify the organoleptic qualities of triggerfish nuggets with two different fillers: high-protein wheat flour and white bread. The research method is the experiments with the aim of obtaining a description of the organoleptic quality of triggerfish nuggets. The acquisition of the description results was done with two nugget designs, from two nugget products found the quality of wheat flour triggerfish nuggets with a golden brown color, fishy aroma, good ability, and savory taste. While the quality of triggerfish nuggets with a white bread filler has a golden yellow color, a fishy aroma, excellent find and savory taste. These two types of fillers make a significant difference in the decryption of texture quality or the level of ability of trigerfish nuggets.